Global health and global aging (Jossey-Bass, 2007)
The book covers the fundamentals of global aging and health and provides real-world models from countries and regions that offer the best practices in current approaches. Global Health and Global Aging presents information about leadership and governance challenges as well as insights about aging in different cultures and countries in all regions of the world.